Comparison of Student and Teacher Centered Teaching Strategies in Postgraduate Ophthalmology Trainees - Mohammad Idris; Hasan Yaqoob; Bilqis Dawood; Muhammad Amjad Khan; Eemaz Nathaniel (Pakistan Journal of Medical Research, 2022)
Background: The education of students at the postgraduate level is an essential component of our teaching hospitals, which serve as the primary tertiary referral centers. Self-directed learning readiness is an important part of training and learning.